S−H⋅⋅⋅π Driven Anti‐Markovnikov Thiol‐Yne Click Reaction. Issue 9 (21st August 2018) - Choudhuri, Khokan; Pramanik, Milan; Mandal, Arkalekha; Mal, Prasenjit
Abstract: Herein we demonstrate that an anti‐Markovnikov selective thiol‐yne‐click (TYC) reaction could be achieved between phenyl acetylenes and thiophenols by exploiting a newly identified S−H⋅⋅⋅π non‐covalent interaction without using any catalysts, additives and solvents. Natural bond orbital (NBO) analyses also supported that S−H⋅⋅⋅π and cooperative π–π stacking interactions helped to promote this regioselective reaction. The hydrothiolated products were isolated in near quantitative yields. Also, the concept of self‐sorting was demonstrated when styrene, phenyl acetylene and thiophenols were reacted in one pot. Owing to the stronger S−H⋅⋅⋅π preference of ethynyl≡H over the vinyl=H hydrogen bond, selectively, TYC product formation was found to be dominating over the thiol‐ene‐click (TEC) product. Abstract : It's clicking : By exploiting newly identified weak and non‐covalent S−H⋅⋅⋅π interaction anti‐Markovnikov selective thiol‐yne‐click (TYC) reaction could be achieved without using any catalyst, additive, or solvent.